Kinerja Satpol-PP dalam Menertibkan Pelanggaran Asusila di Kabupaten Sinjai - Zulkifli Arifin; Sukarno Hatta; Syahril Syahril; Adi Nawir; Indra Indra (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Muhammadiyah Sinjai, 2022)
This study aims to find out how the performance of the Civil Service Police Unit of Satpol-PP in controlling immoral behavior in Sinjai Regency. The type of research used is qualitative. The results of the study show that from the point of view of handling complaint reports, action procedures, raids to the handling and resolution of asusia problems. In addition, the reduction in the number of reported immoral violations is currently based on the work system of the civil service police unit of the Sinjai district in involving community participation in providing information/complaints and how the activity procedure goes well.